Defense styles employed by healthcare professionals experiencing compassion fatigue - Tülay Yılmaz Bingöl; Özkök, Zeynep; Nermin Gürhan; Bahadır Geniş; Özge Yaman (KHD-Production, 2025)
The healthcare sector operates under relentless demands, requiring uninterrupted service delivery amid high-stress environments. Compassion fatigue manifests as a complex interplay of burnout and secondary traumatic stress. To mitigate the psychological toll of compassion fatigue, healthcare professionals often adopt defense mechanisms. This study examines the defense styles used by healthcare professionals experiencing compassion fatigue. This study is a descriptive quantitative study. The study sample consisted of 499 actively working healthcare professionals (422 nurses, 77 doctors). A Personal Information Form consisting of 12 questions, the Compassion Scale (CQ), and the Defense Style Questionnaire-40 (DSQ-40) were used to collect data. The study was conducted using the survey method (Online link) and the snowball sampling method. According to the study results, the level of compassion increases as the number of children in the participants increases. The level of compassion decreases as the level of education increases. In addition, it was determined that participants with low levels of compassion resort to immature defense styles and may experience compassion fatigue. In order to prevent compassion fatigue in healthcare professionals who play very important roles in protecting, developing, and improving community mental health, The management should support and support healthcare professionals in problems experienced in clinical environments, improve difficult working conditions, and take measures to prevent violence in healthcare.